ANALISIS KINERJA KARYAWAN PADA PT. BANK SYARIAH MANDIRI CABANG AKSARA MEDAN DITINJAUDARI MANAJEMEN SYARIAH - Anjur Perkasa Alam (Journal Analytica Islamica, 2016)
This study aims to determine how much influence the Education, Culture of organizations, Wages, Work Motivation on Employee Performance of Sharia Mandiri Bank Syariah Mandiri Branch Aksara Medan. The sample in this study are employees of Sharia Mandiri Bank. Forms of this research are form of quantitative study using multiple linear regression analysis supported by models test and statistical tests using SPSS 17 and Eviews 8. From the results of research that conducted at alpha 5%, the authors concluded that the results of multiple linear regression analysis showed that the variables education, organizational culture, wages, work motivation affects the performance of employees simultaneously and together influence employee performance amounted to 71.3%. Variation factors that influence employee performance is jointly explained by education, organizational culture, wages, work motivation, with value effect is 71.3%, meanwhile the residual effect of 28.7% explained by other variables not examined.